Visualized strategy for predicting buildings energy consumption during early design stage using parametric analysis. (September 2017) - Elbeltagi, Emad; Wefki, Hossam; Abdrabou, Saad; Dawood, Mahmoud; Ramzy, Ahmed
Abstract: Recently, there has been a high level of demand for sustainable design of buildings construction. The catalysts for such demand are rising energy costs and increasing environmental concerns. Therefore, it is important to evaluate building energy consumption, which is the key problem of building energy saving. There is a need for a reliable energy simulation model to predict buildings energy consumption. In addition, designers suffer from the limitations of energy simulation tools during the early design stage that addresses buildings envelope and orientation. This study proposes a strategy for visualized parametric energy analysis of buildings during the conceptual design phase. It presents an energy-oriented workflow that accommodates the Egyptian context. A residential building model is developed by coupling parametric analysis and building energy modeling tools as a means of developing an energy consumption database. The parallel coordinate plot is used to visualize the database to allow decision makers to flexibly evaluate energy performance. The advantages of this paper stem from: 1) providing a new strategy for visualizing the predicting building energy consumption data; 2) facilitating the process of decision making for energy design alternatives during early stages; 3) integrating parametric modeling and energy simulation engine in one platform to come over the problem of interoperability; 4) developing a generic model with variant energy simulation parameters; and 5) presenting an automated and simplified approach to enable modelers to simulate and analyze building energy performance with a more timely, accurate and efficient process. Highlights: Conceptual building design considering parametric analysis of energy consumption. Energy simulation tools using EnergyPlus as an energy simulation engine. Coupling both building modeling and energy simulation in one platform. Common building energy efficiency measures available in Egypt. Visualization of energy consumption database using parallel coordinate plot.